Penerapan Model Pembelajaran Learning Cycle 5E dalam Meningkatkan Hasil Belajar Siswa - Jaya, I Komang Gangga Parama; Indrayani, Luh (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study departs from problems in class VII K SMP N 1 Banjar, where student learning outcomes are still relatively low. To overcome these problems research into the application of learning cycle 5e. This study is aimed to determine the increase of sosial studies learning outcomes in class VII K SMP Negeri 1 Banjar through the application of learning cycle 5e of the fourth basic competencies with the material scarcity and human needs, Action, Motif and Economic Principle. The type of the research is Class Action Research (CAR) and the data collected through observation and test method. The type of data is quantitative data.Â  Based on the results of the study stated that the first cycle of student learning outcomes in the first cycle obtain an average learning completeness is 71,44%, then in the second cycle obtain an average learning completeness is 85,44%. Research results prove that sosial studies learning outcomes can increase after applying learning cycle 5e in class VII K SMP Negeri 1 Banjar.